THE BIBLE'S VIEWPOINT OF MAJORAN VARIETIES OVER A PERIOD OF TIME - Qayumov Muslimbek Yo‘ldoshevich (American Journals, 2023)
This article provides valuable information about the manifestation of important farm characteristics of major varieties over a variety of times.
Keywords: major, moyli ekinlar, introduksiya, issiqxona, ko'chatlar.